Game Design Factor Questionerin User Experience Analysis on Selera Nusantara Game - Kathryn Widhiyanti; Kusuma Dewangga; Firas Almukhtar (Indonesian Journal of Information Systems, 2022)
Game products are one of the media to provide pleasure, satisfaction and knowledge for users. Game Selera Nusantara is a game product created by a game studio in Yogyakarta, namely Gambir Studio, created with the aim of providing pleasure, satisfaction and knowledge to its users. In order for the goal of the Selera Nusantara Game to be achieved, a game design by a user-centered game designer is needed. Game Selera Nusantara is a game with the Casual genre that has a target audience of children and teenagers with the main goal of introducing Nusantara cuisine. The good aim of the Selera Nusantara Game which introduces the culture of the archipelago is the basis of this research by assessing the quality of the game so that it can be accepted by the target audience optimally. The User Experience method with Game Design Factor Questionaire and compared with the results of interviews with game designers from Game Selera Nusantara used in this study provides an analysis of the quality of the game quantitatively. The results of the analysis show that Game Selera Nusantara has a high score on the criteria of Game Goals, Game Mechanism, Interaction, Fantasy Game, Narrative, Sensation, Game Value, Mystery, Flow, which is more than 90%. This means that the Selera Nusantara game has been able to fulfill the goal of providing pleasure, satisfaction and knowledge to its users in accordance with the design of the game designer.